Hyperspectral microscopy of subcutaneously released silver nanoparticles reveals sex differences in drug distribution. (February 2022) - Mahdieh, Zahra; Postma, Britten; Herritt, Lou A.; Hamilton, Raymond F.; Harkema, Jack R.; Holian, Andrij
Graphical abstract: Highlights: Hyperspectral microscopy can accurately map low concentration drugs in skin tissue. Silver nanoparticles release from electrospun fibers in long-term implants. Sex differences is seen in hair regrowth and subcutaneous drug distribution in mice. Nanoparticles accumulate in hair follicles in female or dermis layer in male mice. Zinc oxide nanoparticles improve wound healing and hair regrowth. Abstract: Biomaterials have a great potential to improve human health, however in vitro and in vivo studies are necessary to provide information on their efficacy and safety. This study reports on a comprehensive evaluation of core-shell electrospun fibers loaded with silver nanoparticles (Ag NP) where the delivery rate was controlled by different sizes of Ag NP and thermoresponsive poly(n-isopropylacrylamide) (PNIPAM) hydrogel particles. Fiber meshes also contain zinc oxide nanoparticles (ZnO NP), to improve pore structure for controlled release of Ag NP. In vitro cytotoxicity studies using cultured human A549 epithelial cells demonstrated that the ZnO NP component, which is known to cause cytotoxicity, of the fiber meshes did cause measurable cell death. In vitro antibacterial efficacy of the fiber meshes was shown with rapid and efficient growth inhibition in E. coli bacterial culture. Fiber meshes were implanted subcutaneously for up to 27 days in male and female C57BL/6 mice to evaluate the in viv o drug release and biocompatibility. Hyperspectral microscopy was used as an advanced tool to determine precise location of released Ag NP into the skin compared to the conventional tissue staining methods. Results suggested that Ag NP were continuously released over 27 days of implantation in mice. Hyperspectral imaging revealed that released Ag NP dispersed in the dermis of male mice, however, Ag NP accumulated in the hair follicles of female mice (Figure). Mice implanted with fiber meshes containing ZnO NP had better hair regrowth and wound healing, which was in contrast to in vitro cytotoxicity results. These findings suggest that these newly developed fiber meshes can have unique long-term release of drugs loaded in the fiber core and appear to be biocompatible. The differences in the sex-bias outcome suggest the opportunity for development of sex-specific drug delivery systems.